BASES AND FOUNDATIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In order to design and build foundations not only economically, but, most importantly, reliably, it is necessary to clearly understand how the loads from structures are transmitted to soils, the peculiarities of the behavior of soils under the action of compressive, pulling and shearing loads on them, how the properties of different soils change when water acts on them, which foundations and in which soils should be used, by what methods to erect them. Answers to the listed and many other questions can be obtained from the study of the subject "Bases and Foundations."